Prenatal and Newborn Immunoglobulin Levels from Mother-Child Pairs and Risk of Autism Spectrum Disorders - Grether, Judith K.; Ashwood, Paul; Van de Water, Judy; Yolken, Robert H.; Anderson, Meredith C.; Torres, Anthony R.; Westover, Jonna B.; Sweeten, Thayne; Hansen, Robin L.; Kharrazi, Martin; Croen, Lisa A. (Frontiers in Neuroscience, 2016)
Background. An etiological role for immune factors operating during early brain development in children with autism spectrum disorders (ASD) has not yet been established. A major obstacle has been the lack of early biologic specimens that can be linked to later diagnosis. In a prior study, we found lower risk of ASD associated with higher levels of maternally-derived total IgG and Toxoplasmosis gondii (Toxo) IgG in newborn blood spot specimens from children later diagnosed with ASD compared to population controls. Methods. We obtained maternal mid-gestational serum specimens and newborn screening blood spots from the California Genetics Disease Screening Program (GDSP) for linked mother-baby pairs for 84 children with ASD and 49 children with developmental delay but not ASD (DD) identified from California Department of Developmental Services records and for 159 population controls sampled from birth certificates. Immunoglobulin levels in maternal and newborn specimens were measured by solid phase immunoassays and analyzed in logistic regression models for total IgG, total IgM, and Toxo IgG, and, for maternal specimens only, Toxo IgM. Correlations between maternal and newborn ranked values were evaluated. Results. In both maternal and newborn specimens, we found significantly lower risk of ASD associated with higher levels of Toxo IgG. In addition, point estimates for all comparisons were <1.0 suggesting an overall pattern of lower immunoglobulin levels associated with higher ASD risk but most did not reach statistical significance. We did not find differences in maternal or newborn specimens comparing children with DD to controls. Discussion. These results are consistent with evidence from our prior study and other published reports indicating that immune factors during early neurodevelopment may be etiologically relevant to ASD. Lowered immunoglobulin levels may represent suboptimal function of the maternal immune system or reduced maternal exposure to common infectious agents. Conclusion. Patterns seen in these selected immunoglobulins may provide clues to mechanisms of early abnormalities in neurodevelopment contributing to ASD. We recommend further study of immunoglobulin profiles in larger samples of linked mother-baby pairs to evaluate possible etiologic relevance.